Vitamin B12 Deficiency Is Prevalent Among Czech Vegans Who Do Not Use Vitamin B12 Supplements - Selinger, Eliška; Kühn, Tilman; Procházková, Magdalena; Anděl, Michal; Gojda, Jan (Nutrients, 2019)
As not much is known about the prevalence and predictors of nutritional deficiencies among vegans in the Czech Republic, we evaluated whether supplement use and duration of adherence to the vegan diet are associated with the risk of cobalamin and iron deficiencies. Associations between self-reported supplementation and duration of vegan diet with biomarkers of cobalamin (serum cobalamin, holotranscobalamin, homocysteine, folate) and iron status (serum ferritin, iron binding capacity, transferrin and saturation of transferrin) were assessed by cross-sectional analyses of medical data from a clinical nutrition center. Data from 151 (72 females) adult vegans (age 18-67 years), who were free of major chronic diseases and 85 (40 females) healthy non-vegans (age 21-47 years) were analyzed. Overall, vegans had significantly lower cobalamin, hemoglobin and ferritin levels, but higher folate and MCV values compared to non-vegans. Vegans not using cobalamin supplements were at higher risk of low plasma cobalamin than regularly supplementing vegans (OR: 4.41, 95% CI 1.2-16.16 for cobalamin, OR: 19.18, 95% CI 1.02-359.42 for holotranscobalamin), whereas no significant differences in cobalamin status related to duration of the vegan diet were observed. Regularly supplementing vegans had similar levels of cobalamin/holotranscobalamin as non-vegans. Despite lower ferritin and hemoglobin levels, there was no indication of a higher risk of iron-deficiency among vegans. To conclude cobalamin deficiency risk depends on supplementation status and not on the duration of an exclusive vegan diet, which underlines the need to integrate cobalamin status monitoring and counselling on supplement use in routine clinical care in the Czech Republic.
Keywords: Male; prevalence; nutriční stav; anemie z nedostatku železa; Nutritional Status; Vitamin B 12; Young Adult; Diet, Vegan; Vegans; nedostatek vitaminu B12; vitamin B 12; Dietary Supplements; kyselina listová; Adult; mladý dospělý; Folic Acid; Česká republika; ženské pohlaví; Cross-Sectional Studies; Czech Republic; potravní doplňky; Aged; Middle Aged; Anemia, Iron-Deficiency; lidé středního věku; Adolescent; dieta veganská; Humans; senioři; Female; ferritiny; dospělí; mužské pohlaví; mladiství; vegani; lidé; Prevalence; průřezové studie; Vitamin B 12 Deficiency; Ferritins